Polityka zagraniczna Federacji Rosyjskiej w latach 90-tych. Kontekst historyczno-ideowy - Jedliński, Marek (Środkowoeuropejskie Studia Polityczne i Medioznawcze, 2009)
The author highlights that Russia has ceased to be the liberator and the stronghold of the global revolution, the leader of the bloc, the defender of the ‘only right ideology’ and the model of a political system for other states, it was the times of the USSR. This realization Moscow continuously pursue policy to regain its position on the international arena. It is unlikely, however, that Russia will be able to fulfill her ambition by means of territorial expansion: the primary role of the economy inern international relations allows us to assume that Russia will not decide to enter an open confrontation with theWest as she is gradually made increasingly more dependent onWestern financial centers.